2007
DOI: 10.1111/j.1532-5415.2007.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Access to Primary Care for Medicare Beneficiaries

Abstract: Medicare beneficiaries' access to primary care is limited and varies significantly by region, population size, and type of provider.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A recent report released by the American Hospital Association examining trends in ED use by Medicare beneficiaries between 2006 to 2010 showed a number of factors contributing to this, including rising severity of illness of beneficiaries receiving ED care, greater use of ED services by people dually eligible for Medicare and Medicaid who are generally sicker with multiple chronic conditions, and increasing use of ED services by beneficiaries with behavioral health diagnoses who require higher intensity of services. 18 While the number of primary care clinics accepting Medicare remains strong, there is recent evidence to suggest that practices accepting new Medicare patients are dwindling, 19 with many patients still unable to access clinics after business hours. 20 A combination of these factors is likely contributing to the overall increasing ED visit rates for falls as well.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report released by the American Hospital Association examining trends in ED use by Medicare beneficiaries between 2006 to 2010 showed a number of factors contributing to this, including rising severity of illness of beneficiaries receiving ED care, greater use of ED services by people dually eligible for Medicare and Medicaid who are generally sicker with multiple chronic conditions, and increasing use of ED services by beneficiaries with behavioral health diagnoses who require higher intensity of services. 18 While the number of primary care clinics accepting Medicare remains strong, there is recent evidence to suggest that practices accepting new Medicare patients are dwindling, 19 with many patients still unable to access clinics after business hours. 20 A combination of these factors is likely contributing to the overall increasing ED visit rates for falls as well.…”
Section: Discussionmentioning
confidence: 99%
“…Access to care for elderly Medicare beneficiaries may pose different challenges for the health care delivery system. A study found significant variations across all 4 US regions in PCPs’ willingness to accept new Medicare patients 20 . CHF is the leading cause of hospitalization for the Medicare population.…”
Section: Discussionmentioning
confidence: 99%
“…A study found significant variations across all 4 US regions in PCPs' willingness to accept new Medicare patients. 20 CHF is the leading cause of hospitalization for the Medicare population. The elderly population in the United States is projected to more than double, from approximately 12% of the US population in 2000 to 20% in 2030.…”
Section: Discussionmentioning
confidence: 99%
“…Gaps in transitions in care from the inpatient to the outpatient context may account for many of the observed readmissions, especially amongst non-privately insured patients (Medicare, Medicaid, and uninsured patients) who may experience difficulty in accessing outpatient care. 12,13 …”
Section: Commentmentioning
confidence: 99%